Breaking Free: the fight for equal pay in the prison service notes by the Public and Commercial Services Union (PCS) (2008)
2008 "Breaking Free: the fight for equal pay in the prison service notes by the Public and Commercial Services Union (PCS)", 2008, Public and Commercial Services Union Click PDF icon to read notes on the film Breaking Free.